2016
DOI: 10.7883/yoken.jjid.2015.267
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of G12 Human Rotaviruses in Children with Gastroenteritis in Myanmar

Abstract: SUMMARY: Human rotavirus samples from 54 children with acute gastroenteritis in Myanmar in 2011 were subjected to reverse transcription-PCR to determine their G and P types. On G typing, G2 (24/54; 44.4z) was found to be the most prevalent, followed by G12 (17/54; 31.5z) and G1 (1/54; 1.9z). Mixed cases with G2 and G12 were found in 12 of the 54 (22.2z) samples. On P typing, P[4] was found to be the most predominant (29/54; 53.7z), followed by P[8] (17/54; 31.5z) and P[6] (4/54; 7.4z). Mixed cases with P[4] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The G12 genotype was first detected in children with diarrhoea in the Philippines during 1987-1988, and was subsequently reported from Thailand and USA (1998)(1999), and from India in 2003 from the eastern region [30][31][32][33]. In the following years, G12 was reported from other geographical regions of India also [20,34], and from neighbouring countries such as Nepal, Myanmar, Bangladesh, and Sri Lanka [35][36][37][38][39][40][41][42][43]. During 2005 to 2013, studies on rotavirus diarrhoea in hospitalized children from different continents including Asia found that G12 positivity ranged from 10 to 86% of rotavirus gastroenteritis [44].…”
Section: Discussionmentioning
confidence: 98%
“…The G12 genotype was first detected in children with diarrhoea in the Philippines during 1987-1988, and was subsequently reported from Thailand and USA (1998)(1999), and from India in 2003 from the eastern region [30][31][32][33]. In the following years, G12 was reported from other geographical regions of India also [20,34], and from neighbouring countries such as Nepal, Myanmar, Bangladesh, and Sri Lanka [35][36][37][38][39][40][41][42][43]. During 2005 to 2013, studies on rotavirus diarrhoea in hospitalized children from different continents including Asia found that G12 positivity ranged from 10 to 86% of rotavirus gastroenteritis [44].…”
Section: Discussionmentioning
confidence: 98%